Transthoracic guidance of percutaneous tricuspid valve repair: a case report. Issue 12 (11th November 2021) - Patrascu, Alexandru; Binder, Donat; Polleit, Benjamin; Ott, Ilka
Abstract: Background: Percutaneous tricuspid valve (TV) repair for tricuspid regurgitation (TR) is arising as a viable treatment option in high-risk patients and can lead to symptom control an improvement in quality of life (QoL). Newest devices have greatly increased safety and efficacy of interventional TR therapy. However, as with any emerging medical procedure, safety aspects need to be considered and procedural risks gradually reduced. Case summary: We present the case of an 87-year-old woman with massive TR despite successful percutaneous mitral valve repair. The patient was turned down for surgery and eventually underwent percutaneous TV repair using the TriClip™ (Abbott Medical) device. Significant TR reduction with sustained procedural success at 30-day follow-up were associated with functional and clinical improvement. Transthoracic echocardiographic guidance of the procedure, thanks to excellent parasternal TV visualization, is highlighted, while the complex anatomy of the TV is pointed out. Discussion: Tricuspid regurgitation is an individual predictor of morbidity but frequently found in elderly patients who are deemed very high risk for surgical treatment. This case underscores the use of modern interventional techniques and devices for addressing TR and improving QoL, whether as a stand-alone procedure or as part of complete interventional therapy of the atrioventricular valves.